Sexual disorders in chronic salpingo-oophoritis as a variant of the biopsychosocial model - Vladislav G. Konovalov; Vladimir D. Mendelevich (IP Berlin A.V., 2021)
Background. Modern gynecology uses all the latest achievements of other medical, basic natural sciences and medical technologies. However, sexopathology in women with gynecological diseases, due to the complexity of etiopathogenesis, remains poorly understood. Aim. Development of a diagnostic algorithm and identification of the structure of sexual disorders (SD) in chronic salpingo-oophoritis (CSO). Materials and methods. We examined 100 gynecological patients aged 1838 (on average 27.31.2) years with a diagnosis of CSO (N70.1 according to ICD-10), 67% of whom had sexual dysfunctions. Research methods: clinical-psychopathological, psychometric, experimental-psychological, sexological, gynecological, statistical. Results. SD which are present in 67% of women with CSO, are more often (40.3%) of a mixed nature. Neurotic disorders are represented by somatoform (F45) 29.9%; anxiety-phobic (F40) 22.4%; conversion (F44) 14.9% disorders and neurasthenia (F48.0) 7.5%. Conclusion. The severity of the course of CSO does not always correspond to the level of manifestations of sexual dysfunction; the predominant sexual dysfunction is dyspareunia (54%). Somatogenic asthenia, which according to ICD-10 refers to mental disorders, is reduced by purely somatic (gynecological) therapy. The tactics of gynecologists to identify sexual dysfunctions in women with gynecological diseases have been determined. An in-depth analysis of SD in CSO has been carried out in two main directions (sexo gyneco) in the domain of science (logy) as a variant of the modern biopsychosocial model proposed in ICD-11.